trabalhodoprofessor@chateducacional.com.br: aportes para compreender o trabalho do professor iniciante em EAD - Abreu-Tardelli, Lília Santos (2006)
This research aims at contributing to the understanding of the work of a professor beginning to work in Distance Education, based on the analysis and interpretation of the representations about her acting in texts produced about and in the work situation in Distance Education, specifically in the context of the educational chat. In order to do that, we adopt the theory and methodology of sociodiscursive interactionism an interdisciplinary branch of Psychology which gives to acting and language an essential role in human development. Work being a way of acting, institutionally ruled and taking a central role in human development, we set out to investigate the relationship between language (constitutive of the human being) and work (central axis to understand present day society) in Distance Education within the different levels in which this work takes shape. With that in mind, we present a synthesis of the theoretical and methodological frame that we adopt and which involves: a) sociological issues the concept of work and technology and their mutual relations in contemporary society; b) issues about the status of actions and activities and their relations with language; c) issues related to the method of collection and analysis. Concerning the method of collection and analysis, we first present an a priori classification of the texts that constitute our data, and which allowed us to collect texts considered as (re-)configurating the acting of a first-time professor in an online course. After that, the categories of analysis are presented aiming at identifying the characteristics of these texts or of some of their segments in their general, organizational, enunciative and semantics aspects. The analyses of the texts aim at the understanding of the relations that this discursive or textual network bears with the work of a first-time professor in Distance Education, in his/her different ways of acting. Finally, the results of the analyses are presented, as well as the conclusions reached through the analyzed texts both in regard to the acting of the professor in a Distance Education environment and the methodological and theoretical frame adopted